Fast estimation method of renewable energy carrying capacity of power grid based on nadir frequency constraint. Issue 1 (June 2021) - Jiang, Xiaoliang; Xie, Yan; Si, Ruihua; Tang, Xiaojun; Yu, Linlin; Li, Jing
Abstract: With more and more renewable energy connected to the power system, the power system gradually presents the characteristics of low inertia and the risk of frequency instability gradually becomes prominent. Therefore, nadir frequency has become one of the limiting factors of renewable energy carrying capacity. In this paper, firstly, based on the swing equation, frequency dynamic response after power loss was analysed. Secondly, quantitative analysis on system inertia time with renewable resources was carried out, with higher penetration rate k and the replacement rate a, the inertia time is relative lower. Thirdly, fast estimation method of renewable energy carrying capacity of power grid based on nadir frequency constraint was proposed. Finally, taking a regional power grid as an example, the effectiveness of the proposed estimation method is verified.